Information literacy in Europe: a literature review - Sirje Virkus (Information Research: An International Electronic Journal)
Examines the developments in information literacy in Europe and provides an overview of the concepts used and discussed by European authors. Some examples of information literacy initiatives in schools and the higher education sector, as well as of institutions and organizations, projects and conferences concerned with information literacy, are given. Some research initiatives are also introduced. The overview is based on literature reviews and personal observations and involvement and presents a selective review.